Ideas sobre los cambios de estado de agregación y las disoluciones en alumnos del 2º curso del BUP - Fernández Fernández, J. M. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
We have tried to learn from the pupils who start in our school the systematic study of Chemistry, which are their ideas about nature and mass preservation, in relation to changes in substance condition and solution of a solid in a liquid. We have learnt that a great majority of them have preconceptions about the above mentioned questions, however, those preconceptions do not form a solid and coherent structure, thus showing an important confusion of ideas.